Epithelial-Mesenchymal-Transition-Like Circulating Tumor Cell-Associated White Blood Cell Clusters as a Prognostic Biomarker in HR-Positive/HER2-Negative Metastatic Breast Cancer - Guan, Xiuwen (Front Oncol, 2021)
BACKGROUND: Although positive Circulating tumor cells (CTCs) status has been validated as a prognostic marker in breast cancer, the interaction between immune cells and CTCs during the progress of Epithelial-mesenchymal-transition (EMT), and the clinical implications of CTC-associated white blood cell clusters (CTC-WBC clusters) for metastatic breast cancer are largely uncharacterized. METHODS: We optimized a filter-based method combined with an RNA in situ hybridization technique according to the epithelial- and mesenchymal-markers to analyze EMT in CTC-WBC clusters. Serial peripheral blood samples from 135 patients with Hormone receptor (HR)-positive/HER2-negative metastatic breast cancer receiving first-line chemotherapy with docetaxel plus capecitabine were prospectively collected until disease progression from Nov 2013 to March 2019. Follow-up data collection was conducted until July 2020. RESULTS: A total of 452 blood samples at all time-points were collected and analyzed. Median age of the cohort was 51.0 years (range, 27 to 73 years), and most of them (76.3%) had visceral metastases. Median progression-free survival (PFS) was 10.6 months (95% CI, 8.8 to 12.3 months). The presence of EMT-like CTC-WBC clusters was more frequently evident among patients with simultaneous bone and lymph node metastases (87.5% vs 36.2%, P=0.006), whereas no associations were observed between CTC-WBC clusters and other clinicopathologic characteristics before chemotherapy. The patients with EMT-like CTC-WBC clusters tended to show a significantly increased number of total CTC count (median,19.0 vs 5.0, P<0.001). The patients with at least one detectable EMT-like CTC-WBC cluster at baseline were characterized by significantly worse PFS, when compared to the patients with no EMT-like CTC-WBC clusters detected (7.0 vs 10.7 months, P=0.023), and those with five or more epithelial-based CTCs detected per 5mL of peripheral blood (7.0 vs 12.7 months, P=0.014). However, the total CTC-WBC clusters were not correlated with patients’ survival in the cohort (8.4 vs 10.6 months, P=0.561). CONCLUSIONS: Our data provide evidence that the emergence of CTC-WBC clusters underwent EMT before treatment is associated with significantly poorer PFS in HR-positive/HER2-negative metastatic breast cancer patients receiving docetaxel plus capecitabine, which may be used as a parameter to predict the clinical outcomes and a potential target for individualized therapy.